(untitled) - Sarah, Duchess of York; Duchess of York; 1959-; Williams, Sam; 1955- (New York, 2003)
While on a picnic with four friends, a plucky doll named Little Red decides to investigate a noise that doesn't sound very friendly.
3-6.
Accelerated Reader AR